Fruitless and doublesex coordinate to generate male-specific neurons that can initiate courtship. - Kimura, K.; Hachiya, T.; Koganezawa, M.; Tazawa, T.; Yamamoto, D. (Neuron, 2008)
Biologists postulate that sexual dimorphism in the brain underlies gender differences in behavior, yet direct evidence for this has been sparse. We identified a male-specific, fruitless (fru)/doublesex (dsx)-coexpressing neuronal cluster, P1, in Drosophila. The artificial induction of a P1 clone in females effectively provokes male-typical behavior in such females even when the other parts of the brain are not masculinized. P1, located in the dorsal posterior brain near the mushroom body, is composed of 20 interneurons, each of which has a primary transversal neurite with extensive ramifications in the bilateral protocerebrum. P1 is fated to die in females through the action of a feminizing protein, DsxF. A masculinizing protein Fru is required in the male brain for correct positioning of the terminals of P1 neurites. Thus, the coordinated actions of two sex determination genes, dsx and fru, confer the unique ability to initiate male-typical sexual behavior on P1 neurons.